TAWAKKAL SEBAGAI SUMBER KEBAHAGIAAN HIDUP Telaah Pemikiran Badiuzzaman Said Nursi dalam al-Kalimāt aṣ-Ṣhaghirah fil-‘Aqīdah wal-‘Ibādah - Muhammad Iqbal Rahman (STAI Darussalam Lampung, 2022)
Abstract This article attempts to describe Said Nursi's thoughts on tawakkal as a source of happiness in al-Kalimat aṣ-Ṣhaghirah fil-'Aqīdah wal-'Ibādah. This reflection is present because humans as poor and helpless (inferior) creatures need provisions to face the uncertainties life. What humans do and strive for does not always run smoothly, sometimes they meet failure and failure in turn weakens humans. Leaning on others brings nothing but regret and disappointment. Being leaning on a higher (God, superior), although criticized for being the cause of the decline of the times, in fact can be a very strong foundation for those who believe in it. The main question in this paper is